Consumer Loyalty: The Effect of Consumer Satisfaction in Mediating E-Trust and Brand Image: Study of Shopee Scarlett Whitening Product Consumers - Putri Dewi Oktavianingsih; Nur Laili Fikriah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This study investigates the mediating role of Consumer Satisfaction in the relationship between E-Trust and Brand Image in relation to Consumer Loyalty. Utilizing a quantitative approach, the research focuses on Scarlett Whitening users who shop on Shopee, with a sample size of 200 respondents selected through non-probability sampling. Data is collected via a digitally administered questionnaire and analyzed using SmartPLS. The findings reveal several significant relationships: Brand Image significantly enhances Consumer Satisfaction, while also having a notable influence on Consumer Loyalty. E-Trust is shown to have a positive impact on both Consumer Satisfaction and Consumer Loyalty. Additionally, Consumer Satisfaction positively influences Consumer Loyalty. The study further finds that Brand Image significantly affects Consumer Loyalty through the mediation of Consumer Satisfaction, as does E-Trust. The implications of these findings are substantial for marketing and brand management strategies. Companies should prioritize building a strong Brand Image as it directly enhances Consumer Satisfaction, leading to greater Consumer Loyalty. Moreover, fostering E-Trust is critical, as it not only improves Consumer Satisfaction but also contributes significantly to Consumer Loyalty. Businesses can achieve this by ensuring transparency in their communications, delivering consistent product quality, and establishing a reliable online shopping experience. Furthermore, the results suggest that organizations should actively seek to enhance Consumer Satisfaction, as it acts as a crucial link between E-Trust, Brand Image, and Consumer Loyalty. By focusing on customer feedback and improving service quality, companies can create a more satisfying experience that cultivates loyalty among consumers. Overall, this study highlights the importance of integrating E-Trust and a strong Brand Image into marketing strategies to foster lasting relationships with customers and ultimately drive sales growth.